Acid stress, anaerobiosis and gadCB: lessons from Lactococcus lactis and Escherichia coli - Small, Pamela L.C; Waterman, Scott R (Trends in microbiology (Regular ed.), 1998)
Bacteria employ multiple strategies for maintaining neutral cytoplasmic pH (pH sub(i)) despite an acidic external environment. Although the mechanisms for maintaining pH homeostasis are not fully understood, the genetic basis of these systems has been the subject of intense investigation in the past few years.